Internet addiction and its relationship with mental disorders in adolescents - Sokolowski, Fabriti Rivelto (2025)
Introduction: Adolescence is a challenging period for the construction of identity and personality. The easy access to and deliberate use of the Internet can lead to various mental health disorders in adolescents. Objective: To quantify the prevalence of Internet addiction and to analyze its impact on the development and/or maintenance of mental health disorders in adolescents. Method: CEP opinion and TCLE were delivered. The study was carried out with high school students from public schools in Passo Fundo (RS), in November and December 2023. Questionnaires containing sociodemographic and behavioral characteristics were applied, along with two tests: the Internet Addiction Test [1] and the Depression, Anxiety, and Stress Test [2]. Absolute and relative frequencies of the dependent and independent variables were calculated, as well as the prevalence of Internet addiction and its relationship with disorders and other variables. Results: The sample (n=139) is predominantly composed of women (53.2%), 16-year-olds (47.5%), white individuals (61.2%), and those from low-income families (33.1%). Regarding internet usage: 75.5% spend more than 3 hours per day online, and 89.2% use smartphones to access the Internet. Seventeen percent exhibit some degree of Internet addiction; 42% show symptoms consistent with anxiety disorder; 25% display signs of depression; and 22% show indications of stress. A positive association was found between depression, anxiety, stress, and internet addiction (p<0.05). Conclusion: Internet addiction is associated with the development or maintenance of mental health disorders. Its negative impact on mental health is evident, highlighting the need for measures aimed at better support and guidance for adolescents.